Evaluasi Regulasi Perlindungan Data Pribadi di Indonesia: Komparasi dengan GDPR Uni Eropa - Karnedi, Gunawan; Alam, RG Guntur (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to evaluate the effectiveness of Indonesia’s Personal Data Protection Law No. 27 of 2022 (UU PDP) by comparing it to the European Union’s General Data Protection Regulation (GDPR) as an international benchmark. Using a normative and comparative legal approach, this research identifies the strengths and weaknesses of Indonesia’s legal framework in safeguarding personal data. The findings reveal that while UU PDP marks a significant step forward in acknowledging data subject rights and introducing legal sanctions, it still lacks comprehensive regulatory mechanisms. Critical areas such as data portability rights, the principle of privacy by design, and clear cross-border data flow regulations remain underdeveloped. Moreover, the absence of an independent supervisory authority limits the enforcement and accountability of the law. Compared to the GDPR, Indonesia’s PDP law remains in its early stages of implementation and requires further harmonization with global standards. The study recommends the establishment of an independent data protection authority, issuance of detailed implementing regulations, incorporation of modern data protection principles, and institutional capacity building. With these improvements, Indonesia’s data protection regime can become more robust, effective, and aligned with international best practices.